KINERJA KEUANGAN YANG MEMBEDAKAN KINERJA KEUANGAN YANG MEMBEDAKAN TINGGI RENDAHNYA HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Suartama, Komang Arik; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 6 No 12 (2017), 2017)
The purpose of this research is to examine the financial ratio (Current Ratio, Debt to Equity Ratio, Total Turn Over Assets, Return On Assets, and the Dividend Payout Ratio) which is able to distinguish the group share price high and low stock price group. This research was done at the manufacturing companies listed on the BEI. The population in this research as much as 144 manufacturing company. Samples taken by using purposive sampling technique, where the manufacturing company has profit a positive and distribute dividends as a sample of 47 research company. Analytical techniques used are analysis of Z-Score and discriminant analysis. Based on the results of the analysis it was found that the ratio-financial ratio (Current Ratio, Debt to Equity Ratio, Total Turn Over Assets, Return On Assets, and the dividend Payout Ratio) can distinguish groups of high stock prices and low stock prices on manufacturing companies. Total Assets Turn Over is a financial ratio that dominates in the determination of group level stock prices higher and stock prices lower.